Quantifying force and positional frequency bands in neurosurgical tasks. Issue 2 (June 2016) - Maddahi, Yaser; Ghasemloonia, Ahmad; Zareinia, Kourosh; Sepehri, Nariman; Sutherland, Garnette
Abstract To establish the design requirements for an MR-compatible haptic hand-controller, this paper measures magnitudes and frequency bands of three mechanical motion and interaction components during the performance of neurosurgical tasks on a cadaveric brain. The hand-controller would allow the performance of virtual neurosurgical tasks within the bore of a high field magnet during image acquisition, i.e., functional MRI. The components are the position and the orientation of a surgical tool, and the force interaction between the tool and the brain tissue. A bipolar forceps was retrofitted with a tracking system and a set of force sensing components to measure displacements and forces, respectively. Results showed working positional, rotational, and force frequency bands of 3, 3 and 5 Hz, respectively. Peak forces of 1.4, 2.9 and 3.0 N were measured in the Cartesian coordinate system. A workspace of 50.1 × 39.8 × 58.2 mm3 and orientation ranges of 40.4°, 60.1° and 63.1° for azimuth, elevation, and roll angles were observed. The results contribute in providing information specific to neurosurgery that can be used to effectively design a compact and customized haptic hand-controller reflecting characteristics of neurosurgical tasks.